Karakteristik Kualitas Tidur Pasien ESRD yang Menjalani Hemodialisis - Tri Wahyuni; Nelwati Nelwati; Rahmiwati Rahmiwati (Jurnal Keperawatan Silampari, 2022)
This study aims to describe the sleep quality characteristics of ESRD patients undergoing Hemodialysis at dr. Bratanata Jambi. This research method is observational research with a descriptive approach. The results showed that based on the characteristics of ESRD undergoing Hemodialysis, the majority were female (61.10%), the mother's education level was low (58.35%), the average duration of Hemodialysis was 3.72 Â± 1.17, the average age average 53.33 Â± 4.35. In conclusion, the characteristics that affect the sleep quality of ESRD patients undergoing Hemodialysis are gender, low level of education, age 45-59 Keywords: Hemodialysis, Sleep Quality, Duration of HD, Education, Age